Analysing the influence of raster angle, layer thickness and infill rate on the compressive behaviour of EVA through CNC-assisted fused layer modelling process. (May 2021) - Kumar, Narendra; Kumar Jain, Prashant
The current study analyses the compressive behaviour of ethylene vinyl acetate specimens processed through extrusion-based additive manufacturing. The compression specimens have been fabricated using an in-house developed fused layer modelling process. Response surface methodology technique has been adopted to generate the experimental runs by selecting raster angle, layer thickness and infill percentage as input process parameters. Further, analysis of variance has been used to analyze the obtained compression data. The infill percentage is found to be the most significant parameter for compressive strength; however, raster angle has shown an insignificant effect. The empirical relation has been established between the selected input process parameters and compressive strength. The predicated and experimental results have also been compared to validate the derived empirical model. Results showed good conformity.